Ludwig's angina: A diagnostic and surgical priority. (April 2020) - Vallée, Maxime; Gaborit, Benjamin; Meyer, Jérémy; Malard, Olivier; Boutoille, David; Raffi, François; Espitalier, Florent; Asseray, Nathalie
Highlights: Ludwig's angina is a frequently fatal rapidly progressive necrotizing cellulitis of the floor of the mouth, the throat and the neck. Ludwig's angina should not be confused with Lemierre's syndrome, different in terms of pathophysiology and therapeutic. We present four cases of severe necrotizing cervical cellulitis notably associated to concomitant self-medication with NSAIDs. To treat anaerobic bacteria and streptococci, B-lactams(penicillin with βL ase inhibitors) +/- combination with clindamycin, should be used. Abstract: Ludwig's angina has been known for two centuries as a rapidly and frequently fatal progressive gangrenous cellulitis or necrotizing fasciitis of the neck and the floor of the mouth. The management of the usually young patients affected requires a trained team combining medical skills in surgery, antibiotic therapy, and resuscitation. The prognosis is directly related to early surgical debridement and the experience of the team managing these patients. We present four cases of severe necrotizing cervical cellulitis notably associated with concomitant self-medication with non-steroidal anti-inflammatory drugs. Through these cases, we conclude that several surgical steps could be required, combined with broad-spectrum antibiotic therapy. An optimal surgery, draining all collections and excising all necrotic tissues, seems to be a condition needed for antibiotic efficacy and finally healing.